Haloperidol attenuates beta-amyloid-induced calcium imbalance in human fibroblasts - Palotás András (SKIN PHARMACOLOGY & PHYSIOLOGY, 2004)
Background: Antipsychotics are widely used in the treatment of behavioral and psychological symptoms of dementia. A low frequency of Alzheimer's disease in patients with schizophrenia is reported, and it has been proposed that antipsychotic medications, such as haloperidol, may be responsible. Disruption of intracellular calcium levels is considered to play a key role in beta-amyloid-induced neurotoxicity in Alzheimer's disease. Haloperidol has also been reported to interact with calcium homeostasis through dopamine-2 and sigma-1 receptors, and other, yet unknown mechanisms. Objective: Therefore, we investigated whether differences in the basal intracellular free calcium levels of cultured cutaneous fibroblasts - cells that do not express dopamine-2 and sigma-1 receptors - derived from sporadic Alzheimer patients and from age-matched control individuals after haloperidol treatment might be present. Methods: Intracellular calcium level was measured in Fura-2AM-loaded human fibroblasts by dual wavelength spectrofluorimetry. Results: Alzheimer cells exhibited significantly lower calcium level as compared to the control cultures. Exposure of fibroblasts to beta-amyloid peptide resulted in increased calcium concentration of the control cells, but not of Alzheimer fibroblasts. Co-incubation of cultures with a therapeutic dose of haloperidol blocked the beta-amyloid-induced elevation of calcium. Conclusion: This finding indicates that haloperidol efficiently countervails ionic imbalance and suggests that it may serve as a potential agent in alleviating neurotoxic effects of beta-amyloid peptide.